Comparison of direct and indirect nursing care time in 8-hour and 12-hour shifts - Raeissi, pouran; Nasiripour, amir ashkan; Reisi, nahid (Advances in Nursing & Midwifery, 2015)
Abstract Introduction: Nurses are the largest and one of the most important groups of health care providers. The quality of health care mostly depends on the quality of direct and indirect nursing care. Measuring the average nursing care time is an objective measure for assessing the quality of patient care.The goal of the present study was to compare the time being devoted to professional – nonprofessional activities by nurses in 8 hours and 12 hours working shift in Shahid Modarres teaching hospital in Tehran. Methods: A descriptive- comparative study was conducted on 30 nurses (27 female, and 3 male) working in medical and surgical wards of Shahid Modarres teaching hospital in Tehran. The nurses were working 8 and 12 hours shifts and in rotating schedule. Data were collected by direct observation of nurses’ activities,using a checklist with list of direct, indirect and nonprofessional nursing activities. The reliability of the checklist was assured by calculating inter observers’ agreement (The duration of time which nurses spent for each activity was recorded. Data were analyzed using SPSS and Wilcoxon test. Results: The findings of the present study revealed that, nurses working 8 hour shift duration, spent 64.99% of their time on professional and 35.3% on nonprofessional activities (41.21% on direct nursing care, 23.78% on indirect nursing care, 22.53% on personnel affairs and 12.5% on administrative activities). Nurses with 12 hour shift duration, spent 65.59% of their times on professional activities and 33.92% on nonprofessional activities (41.57% on direct healthcare, 24.02% on indirect healthcare, 20.94% on personnel affairs and 12.98% administrative activities). Conclusion: Nurses working in both 8 and 12 hours shift spend most of their times for professional activities (direct and indirect healthcare) and devote less time to nonprofessional activities (administrative and personal affairs), and these activities are independent of their shift duration Keywords: Working shift, Nurse, Direct nursing care, Indirect nursing care, Teaching hospital REFERENCES Admi H Tzischinslcy O Epstein R et al (2008). Shift work in nursing: Is it really a risk factor for Nurses health and patients safety?. Nursing Economics. 26 (4)250-256 Farquharson B (2013). How much time do nurses actually spend on patient care? An analysis of real-time data across medical and surgical wards. Avaible at: https://www.rcn.org.uk/__data/assets/pdf_ file/0019/512146/2013_RCN_research_3.1.3.pdf French L (1977). The Personal Management Process.6rd ed. Boston: Houghton Mifflin Co. Hagerty B, Spengler C.(1985). Work sampling analyzing nursing staff productivity. The Journal of Nursing Administration. 5(9) 13-20. Heslop L Power R Cranwell K (2014) Building workforce capacity for complex care coordination: A function analysis of workflow activity. Heslopet al. Human Resources for Health2014,12:52. Avaiable at:http://www. human-resources-health.com/content/12/1/52 Josten DC (2003).The effects of extended work days on fatigue, health, performance and satisfaction in Nursing. Journal of Advanced Nursing.44(6) 643-652. Kabiri F (1992) [ How nurses relate themselves to patients in the internal and cardiology wards of Tehran university]. M.S Thesis. Faculty of Nursing and Midwifery Shahid Beheshti University of Medical Sciences. (Persian). Liang Y, Chen W, Lee J & Huang L (2012). Nurse staffing, direct nursing care hours and patient mortality in Taiwan: the longitudinal analysis of hospital nurse staffing and patient outcome study BMC Health Services Research 2012, 12:44 Medical Dictionnary (2014). Avaible At: http://medical-dictionary.thefreedictionary.com/indirect+care. Accessed time: 9/24/2014. Puente LM, Rabbino H (2003). Creating value with strategic resources. Avaiable At:http://www.iseesystems. com/community/connector/Zine/SeptOct03/luz.html. Accessed time: 9/24/2014. Rogers AE, Hwang WY, Scott LS, Aiken LH, Dinges DF(2004). The Working Hours of Hospital Staff Nurses And Patient Safety. Avaiable at:http://content.healthaffairs.org/content/23/4/202.full. Accessed time 9/24/2014. Rostamipoor A(1986).[ Assessment of nurses non professional activities in Tehran hospitals ] M.S Thesis. Tarbiat Modarress university.(Persian). Shams Azad M (1995).[ Comparison of nurses’ productive hours in various wards of educational hospital in Tehran. M.S thesis. Shahid Beheshti University of Medical Sciences. (Persian). Safari M (2002).[ Impact of touching group discussion technique to nurses on the quality of care for myocardial patients]. M.S thesis. Tarbiat Modarress University. [Persian]. 1393 راهب ،84 هرامش ،24 هرود / 50 ناراکمه و یسیئر ناروپ Telles SCR, & Castilho V.(2007). Staff cost in indirect nursing care at an intensive care unit. Rev Latino-am Enfermagem. 15(5) 1005-9 Thompson P (2009). Health care financial management. Health Management Journal.63(1) 76-82. Westbrook JI Duffield C Li L & Creswick NJ (2011) How much time do nurses have for patients? A longitudinal study quantifying hospital nurses’ patterns of task time distribution and interactions with health professionals, BMC Health Services Research 11:319. Avaible at: http://www.biomedcentral.com/1472-6963/11/319 Williams M (1977).Quanification of direct nursing care activities. Journal of Nursing Adminstration. 7(8)15-8, 49-51.